Implementation of Village-Owned Enterprise (BUMDes) Management Policy in Majalengka Regency - Miklas Fajrin Nurcahyo; Udaya Madjid; Anindita Primastuti (Sean Institute, 2026)
The purpose of this study is to identify and analyze the implementation of policies for managing Village-Owned Enterprises (BUMDes), the supporting and inhibiting factors in the implementation of these policies, as well as the efforts made to overcome the inhibiting factors in Majalengka Regency. The theory used as an analytical framework in this study is the policy implementation theory of Van Meter and Van Horn, which emphasizes six main factors: policy standards and objectives, resources, characteristics of implementing organizations, attitudes or dispositions of implementers, inter-organizational communication, and the economic, social, and political environment. This study employs a qualitative approach, with data collection techniques including interviews, observations, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, and conclusion drawing. The informants in this study include the Regent of Majalengka Regency, the Chairperson of Commission I of the Regional House of Representatives (DPRD) of Majalengka Regency, the Sub-district Head of Majalengka, the Village Heads of Cibodas, Sidamukti, Kawunggirang, and Kulur, BUMDes administrators, as well as MSME actors in the research locations. The research locations are focused on Cibodas Village (BUMDes Bina Jaya), Sidamukti Village (BUMDes Rahayu), Kawunggirang Village (BUMDes Kawungwangi), and Kulur Village (BUMDes Tirma). The results of the field study indicate that the implementation of BUMDes management policies in Majalengka Regency has not been carried out optimally. This is due to limited human resources, weak managerial capacity of BUMDes administrators, limited capital, low community participation, and suboptimal guidance and supervision from both local and village governments. In addition, issues remain in policy communication, implementers’ perceptions, and bureaucratic structures that have not fully supported professional and sustainable BUMDes management. The SWOT analysis results show that strengthening human resource capacity, improving institutional governance and monitoring-evaluation systems, optimizing village economic potential, reinforcing the commitment of policy implementers, and enhancing coordination among stakeholders are key strategies to improve the effectiveness of BUMDes policy implementation as an instrument for empowering the village economy.